Coaxiality of Foxb1- and parvalbumin-expressing neurons in the lateral hypothalamic PV1-nucleus - Bilella, Alessandro; Alvarez-Bolado, Gonzalo; Celio, Marco (Neuroscience letters, 2014)
In the ventrolateral hypothalamus, the PV1-nucleus is defined by its population of parvalbumin-expressing neurons. During embryogenesis, the ventrolateral hypothalamus is colonized also by Foxb1-expressing neurons. In adult Foxb1-EGFP mice, many immunofluorescent neurons were found within the region that is occupied by the PV1-nucleus. They formed a cloud around the axial cord of the parvalbumin-immunopositive cells, which they greatly outnumber (3:1). Only a small proportion of the neurons in the PV1-nucleus co-expressed both parvalbumin and Foxb1. In the light of these findings, a redesignation of this lateral hypothalamic structure as the PV1-Foxb1 nucleus would more accurately reflect its specific biochemical properties.
Gesehen am 26.08.2020